Motivasi dan Tantangan Mengajar di Semester Pendek : Studi Kualitatif pada Mahasiswa PPKn Universitas Lambung Mangkrat - Alex Alex; Habibah Pidi Rohmatu; Rahmat Nur; Ismar Hamid; Irsan Irsan; Muh Herisman (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
Short semester programs are one of the academic strategies widely implemented in higher education to accelerate study duration and provide opportunities for grade improvement. This study aims to explore the motivations and challenges experienced by students in attending short-semester courses in the Civic Education (PPKn) Study Program at Lambung Mangkurat University. A qualitative approach was employed using a phenomenological method. Data were collected through semi-structured interviews with 30 students who participated in the short semester during the 2024/2025 academic year. The results indicate that the primary motivations of students include time efficiency, opportunities for grade improvement, and productive use of vacation periods. On the other hand, the challenges faced include dense course materials, limited study time, and minimal learning interaction. These findings highlight the importance of learning innovation and the development of an adaptive curriculum tailored to the characteristics of short-semester programs. This study recommends the formulation of appropriate teaching strategies and specific academic policies to support successful learning during short semesters.